IMPLEMENTASI STRATEGI PEMBELAJARAN INKUIRI PADA PEMBELAJARAN PAI DI KELAS VII SMP NU GONDANGLEGI - Achadah, Alif; Apriani, Mistia (JIPI (Jurnal Ilmiah Pendidikan Islam), 2022)
Learning Islamic religious education is an important education for the human environment. It is also important to instill Islamic values that come from God Almighty to humans. Islamic religious education learning in schools provides teaching materials and keeps students trained in education and learning so that teachers can educate their students to achieve the expected vision, mission and goals. This study aims to explore "the concept of inquiry-based learning at SMP NU Gondan Gurgi" and to realize a complete conceptualized learning. For that, teachers also need to really know the concept of learning that is taught to their students. In addition, teachers need to have inquiry-based learning strategies that are developed while learning so that students can more easily understand the material they are learning. In this case, the application of inquiry-based learning will also be affected, which will make it difficult for children to understand the material provided by the teacher, and will make it easier for children to understand the material. Keywords: Implementation, Inquiry Learning Strategy, PAI Learning